Efektivitas Penggunaan Media Pembelajaran Permainan Tradisional Gobak Sodor Untuk Meningkatkan Kemampuan Motorik Kasar Pada Siswa Tunagrahita Ringan Di SLB YKPC GBKP Alpha Omega (Indonesian Journal for Physical Education and Sport, 2021)
Background:(1) Physical education is a part of education that affects the potential of students in terms of cognitive, affective, and psychomotor which are inseparable from education in general. (2) Gross motor skills are abilities related to the movement of large muscles in controlling body movements through locomotor, non-locomotor, and manipulative abilities. (3) The gobak sodor game can develop children's gross motor skills. Research Questions: (1) Is there an effect of the traditional Gobak Sodor game on pace? (2) What influence does the traditional game of Gobak Sodor have on agility? (3) What effect does the traditional Gobak Sodor game have on reaction speed?. The research method used was an experiment with a "pre-test and post-test group" researchdesign. Mild intellectual students of SLB Alfa Omega with population of16 people, the sample is 16 people with purposive sample technique. The research variables consisted of independent variables, namely the traditional gobak sodor game and the dependent variable, namely the gross motor skills of mild intellectual students. Data analysis was conducted by normality test and homogeneity test. The research results can be concluded: (1) There is an effect of the traditional Gobak Sodor game on pace (running 50 meters) through the pre-test data which has an average of 10.17 and the post-test data has an average of 9.06. By using the paired sample t-test, the sig 2 tailed value was 005. (2) There is an effect of the traditional Gobak Sodor game on agility (Shuttle run) through the pre-test data which has an average of 17.72 and post-test data has an average of 17.00. By using the paired sample t-test, the sig 2 tailed value was 015. (3) There is an effect of the traditional Gobak Sodor game on reaction speed (drop test ruler tool) through the pre-test data which has an average of 32 cm and the post-test data has an average of 24 cm using the paired sample t-test, with a sig 2 tailed value. equal to 044. (4) The results of the data obtained by the experimental group were better than the control group. The researcher's suggestion: teachers are expected to provide simple and attractive learning media for students with mild intellectual so that these students are able to follow and improve their gross motor skills.